THE EFFECT OF EDUCATION THROUGH THE ANIMATED VIDEO "ECAMI" ABOUT ALERTNESS IN TSUNAMI EVACUATION ON THE BEHAVIOR OF ELEMENTARY SCHOOL CHILDREN IN BENGKULU CITY 2021 - Erni Buston; Pauzan Efendi; Mia Amelia (Proceeding B-ICON, 2022)
Calamities are phenomenon that threaten and giving an impact on all ages, including children. Children are a group that is vulnerable to calamities, so it is necessary to make attempt of alertness for the children. One of these attempt is providing the education of alertness in tsunami evacuation to elementary school children using the animated video “ECAMI”. The aim of this study was to determine the effect of education through the animated video "ECAMI" about alertness in tsunami evacuation on the behavior of elementary school children in Bengkulu city 2021. The research design was a quasi-experimental with pre-post test design with control group. The research sample amounted to 44 people consisting of 22 people in the intervention group and 22 in the control group. The sampling technique used is simple random sampling. Analysis using t test within ? ? 0,05. The results showed that the average knowledge before intervention in the intervention group was 69,58 and in the control group was 72,03, therefore the average attitude before intervention in the intervention group was 74,09 and in the control group was 74,64, while the average before intervention in the intervention group 64,91 and in the control group 65,09. The average knowledge after the intervention in the intervention group was 91,78 and in the control group was 84,27, therefore the average attitude after the intervention in the intervention group was 92,45 and in the control group was 87,64, meanwhile the average action after the intervention in the intervention group was 92,73 and in the control group 83,27. The results of the analysis show that there is a difference in the average knowledge with p value 0,000, a difference in the average attitude with p value 0,000, and a difference in the average action with p value 0,002. Educational animation video “ECAMI” can improve the behaviour of alertness in tsunami evacuation.